The impact of Malaysian financial reporting standards on Audit Report Lag - Krouchi, Charafeddine; Abdul Hamid, Fatima; Zainal Abidin , Nor Hafizah (2015)
On 1 August 2008 both The Financial Reporting Foundation (FRF) and the Malaysian Accounting Standards Board (MASB) decided to push the Malaysian listed companies to the full convergence to Malaysian Financial Reporting Standards (MFRSs) starting from the 1st January 2012. This has motivated this research to investigate the impact of MFRS adoption on Audit Report Lag (ARL). The study sample was composed of 238 Malaysian listed companies for the years 2011, 2012 and 2013. The paper used one-way ANOVA analysis and panel data regression to analyze the findings. The results indicate that the MFRS adoption has no significant impact on ARL.